Alinhamento estratégico das atividades de marketing nas indústrias da região metropolitana de Londrina associadas a FIEP - Rocha Neto, Renato da (2010)
This study aimed to ascertain the level of strategic alignment of the marketing area and its activities in the industries of the metropolitan area of Londrina associated with the Federation of Industries of Paraná (FIEP). Thus, defines the strategic alignment for this work, as the consistency between its strategy and external environment and internal organization. This work still part of the premise of a study of the effectiveness of implementation and strategic alignment in the systemic approach. Regarding marketing activities, the study aims to observe five specified activities, and these, marketing organization, marketing information system, segmentation and positioning, marketing mix and strategic marketing planning. Regarding methodology, the research is classified as descriptive, quantitative and cross. The application came from a sample of 88 companies belonging to the register of FIEP. As to conclusions, we highlight the existence of a median line marketing activities, however, with increasing the level of alignment, it also increases the performance of marketing activities. There is equally the limited availability of enterprises in the marketing department, however, with the implementation of activities often in those departments. Although it may be mentioned the low use of marketing activities in industries, so that they are significantly associated with the existence of a specific marketing department.